Factors associated with asthma expression in adolescents - Campos Fernandes, Silvia de Souza (2018)
Objective: To evaluate risk factors associated with asthma symptoms in adolescents in the 13-to 14-year age bracket. Methods: This was a cross-sectional study involving adolescents enrolled in randomly selected public schools in the city of Belo Horizonte, Brazil, and conducted with the use of the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire and its supplementary module for risk factor assessment. The ISAAC questionnaire was completed by the students themselves, whereas the supplementary questionnaire was completed by their parents or legal guardians. Variables showing p <= 0.25 in the univariate analysis were included in the multivariate analysis. Stepwise regression with backward elimination was used for variable selection. Results: We evaluated 375 adolescents, 124 (33.1%) of whom had asthma symptoms. The final multivariate analysis model revealed that asthma symptoms were associated with birth weight < 2,500 g (p < 0.001), day care center or nursery attendance (p < 0.002), maternal history of asthma (p < 0.001), contact with animals during the first year of life (p < 0.027), current contact with animals outside the home (dogs, cats, or farm animals